How do very open economies absorb large immigration flows? recent evidence from Spanish regions - Libertad González Luna; Francesc Ortega (Institute for the Study of Labor (IZA), 2008)
In recent years, Spain has received unprecedented immigration flows. Between 2001 and 2006 the fraction of the population born abroad more than doubled, increasing from 4.8% to 10.8%. For Spanish provinces with above-median inflows (relative to population), immigration increased the high school dropout population by 24%, while only increasing the number of college graduates by 11%. We study the different channels by which regional labor markets have absorbed the large increase in the relative supply of low educated (foreign-born) workers. We identify the exogenous supply shock using historical immigrant settlement patterns by country of origin. Using data from the Labor Force Survey and the decennial Census, we find a large expansion of employment in high immigration regions. Specifically, most industries in high-immigration regions experienced a large increase in the share of low-education employment. We do not find an effect on regions' sectoral specialization. Overall, and perhaps surprisingly, Spanish regions have absorbed immigration flows in the same fashion as US local economies.
Keywords: J2; 330; Immigration; open economies; Rybcszynski; instrumental variables; Einwanderung; Arbeitsangebot; Politik der offenen Tür; Regionaler Arbeitsmarkt; Faktorproportionentheorem; Industrieller Strukturwandel; Schätzung; Spanien; Vergleich; USA